2019
DOI: 10.1186/s13287-019-1490-8
|View full text |Cite
|
Sign up to set email alerts
|

Fetal liver mesenchymal stem cells restore ovarian function in premature ovarian insufficiency by targeting MT1

Abstract: Background: With the development of regenerative medicine and tissue engineering technology, almost all stem cell therapy is efficacious for the treatment of premature ovarian failure (POF) or premature ovarian insufficiency (POI) animal models, whereas little stem cell therapy has been practiced in clinical settings. The underlying molecular mechanism and safety of stem cell treatment in POI are not fully understood. In this study, we explored whether fetal mesenchymal stem cells (fMSCs) from the liver restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 59 publications
0
33
0
3
Order By: Relevance
“…It affects approximately 1% of women under 40 years, which will result in poor infertility outcomes eventually and burden young couples ( 75 , 78 ). POI might be caused by genetic abnormality, aberrant immunity, chemotherapy or radiotherapy, and environmental pollutants ( 79 , 80 ). It is believed that primordial follicles cannot be generated and ovarian reservoir is determined at birth, so the ovarian function is easily compromised by accelerated activation of primordial follicles, depletion of ovarian follicles in the resting pool, and abnormal follicular atresia as shown in Figure 3 ( 81 ).…”
Section: Methodsmentioning
confidence: 99%
“…It affects approximately 1% of women under 40 years, which will result in poor infertility outcomes eventually and burden young couples ( 75 , 78 ). POI might be caused by genetic abnormality, aberrant immunity, chemotherapy or radiotherapy, and environmental pollutants ( 79 , 80 ). It is believed that primordial follicles cannot be generated and ovarian reservoir is determined at birth, so the ovarian function is easily compromised by accelerated activation of primordial follicles, depletion of ovarian follicles in the resting pool, and abnormal follicular atresia as shown in Figure 3 ( 81 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fetal and adult MSCs follow different signaling pathways to execute their functions [ 71 ]. Huang et al [ 72 ] documented that FMSCs could ameliorate ovarian follicular function in a cyclophosphamide-induced mice model via modulation of melatonin membrane receptor 1 and antioxidant enzyme activity. Some of the sources used to derive MSCs used for the treatment of infertility are listed below:…”
Section: Implications For Stem Cells In Infertilitymentioning
confidence: 99%
“…In addition, hUCMSCs restored ovarian function in POI rats by regulating ROS levels through the autophagy-related AMPK/mTOR pathway ( Lu et al, 2020 ). Huang et al (2019) showed that fetal liver MSCs exerted antioxidant effects by lowering ROS levels to restore ovary function in POI models. Moreover, transplanted hPMSCs inhibited oxidative stress in injured ovary by modulating the HO-1/HO-2 ratios in ovarian tissues ( Seok et al, 2020 ).…”
Section: Mechanism Of Mscs-based Treatment For Poimentioning
confidence: 99%